Severe, very early onset preeclampsia in a Covid 19-positive woman with a twin pregnancy presenting with a hydatidiform mole and coexisting normal fetus: a case report - Willy, Daniela; Schmitz, Ralf; Möllers, Mareike; Heitplatz, Barbara; Kuntze, Anna; Stratis, Yvonne; Bahlke, Katrin; Röpke, Albrecht; Meyer-Wittkopf, Matthias; Oelmeier, Kathrin (Frontiers in Medicine, 2024)
Cases of hydatidiform moles with a coexisting fetus are sparse and patients are at high risk for severe complications. Patients and physicians often face the dilemma of the wish to continue pregnancy until viability of the fetus while the risk for maternal complications increases.We present an educational case of a twin pregnancy presenting with a hydatidiform mole and coexisting normal fetus with a placenta praevia. The patient developed severe, early onset preeclampsia with beginning HELLP-syndrome and was tested Covid-19 positive in the further course. Termination of pregnancy was conducted via caesarean section at 18+6 weeks of pregnancy. Histopathology and genetic analysis confirmed a complete hydatidiform mole next to a normal placenta. Close follow-up examinations were conducted and showed normal findings including ß HCG levels normalizing within 5 months. This case combines several rare, difficult and severe medical conditions and demonstrates how an individualized therapy by an interdisciplinary team covering a highly sensitive topic was developed in a situation where no guidelines exist.